2020
DOI: 10.1007/s00431-020-03818-x
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal spectral EEG is prognostic of cognitive abilities at school age in premature infants without overt brain damage

Abstract: Prematurity is a prototype of biological risk that could affect the late neurocognitive outcome; however, the condition itself remains a non-specific marker. This longitudinal 6-year study aimed to evaluate the prognostic role of neonatal spectral EEG in premature infants without neurological complications. The study cohort was 26 children born 23–34 gestational ages; all neonates underwent multichannel EEG recordings at 35 weeks post-conception. EEG data were transformed into the frequency domain and divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 70 publications
2
25
0
1
Order By: Relevance
“…This means that the cognitive profile of children with HIE is not homogeneously lower than that of their peers, but that they show profiles characterized by deficits and preserved functions. This result is in line with our previous work on other preperinatal conditions [27][28][29]. As in those studies, we found high interindividual variability as demonstrated by highly variable scores in the performance of tasks or responses to the questionnaires.…”
Section: Discussionsupporting
confidence: 93%
“…This means that the cognitive profile of children with HIE is not homogeneously lower than that of their peers, but that they show profiles characterized by deficits and preserved functions. This result is in line with our previous work on other preperinatal conditions [27][28][29]. As in those studies, we found high interindividual variability as demonstrated by highly variable scores in the performance of tasks or responses to the questionnaires.…”
Section: Discussionsupporting
confidence: 93%
“…Preterm infants with lower GA may have accelerated brain maturation within 2 weeks after birth, suggesting that preterm infants are prone to brain development abnormalities and brain damage during this period. The results of a one-week aEEG monitoring experiment for deficient birth weight infants starting 12–48 hours after birth confirmed [ 15 ] that early aEEG examination within 1 week after birth can predict the poor prognosis of preterm infants. If it is combined with cranial ultrasonography, it can improve the sensitivity to the poor prognosis of preterm infants.…”
Section: Related Workmentioning
confidence: 79%
“…To the best of our knowledge, our study is the first prospective study to date performed in neonates (in the first week of birth) investigating early non-linear qEEG characteristics (WPLI and complexity measures) and their prognostic value for cognitive outcome at 24 months of age. Furthermore, all studies existing in literature have used the linear qEEG such as coherence (Kühn-Popp et al, 2016), EEG continuity (West et al, 2005), and spectral power (Suppiej et al, 2017;Cainelli et al, 2021), which may not be optimal to capture the complex characteristics of the EEG spectra. Non-linear methods adopted in this study provided deep insight into the underlying brain functions and dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Non-linear methods adopted in this study provided deep insight into the underlying brain functions and dynamics. Several studies investigated the frequency activity underlying EEG by spectrally analyzing the signal using methods that rely on the predefined frequency of traditional brainwaves, as in Kühn-Popp et al (2016), Suppiej et al (2017), andCainelli et al (2021). Prior selection of frequency ranges may result in potentially informative brain waves being missed, specifically in the case of infants, due to the well-known variability between them and older individuals in the neural oscillations of interest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation